Bygones Are Bygones - Brennan, Geoffrey; Hamlin, Alan; Justus Liebig University Giessen (My University, 2009)
`Bygones are bygones' might seem to be an analytic truth, lacking any substantive content. Yet, economists think that, when they state that bygones are bygones, they are asserting something interesting and important. Furthermore, others would argue that the statement `bygones are bygones', when read appropriately, is false. By interrogating the statement `bygones are bygones' we identify a number of key issues relating to rational choice theory and the treatment of intentions, habits and promises. The more philosophical discussion of the things that economists say (and what they might mean) is particularly appropriate in honoring Hartmut Kliemt, much of whose work has brought philosophy and economics into closer proximity.
Keywords: ddc:100; ddc:330